Automatic Measurement Techniques for Compositional Properties of Fresh Concrete: Focus on Water/Cement Ratio and Air Content - Ojala Teemu; Punkki Jouni (Nordic Concrete Research)
Current testing methods for fresh concrete are time-consuming and operator-dependent and, thus, should be replaced with automatic testing methods. This study investigated automated measurement techniques for determining water/cement (w/c) ratio and air content in fresh concrete, addressing this need for more efficient and continuous quality control. The research compared microwave absorption (MWA) and time-domain reflectometry (TDR) techniques for w/c ratio measurement as well as acoustic wave propagation (AWP) technique for air content measurement, against the reference testing methods. Laboratory investigations were conducted on various concrete mix compositions. Results showed that MWA and TDR techniques demonstrated a good correlation with reference methods for w/c ratio (R² = 0.808 and 0.858, respectively), but were sensitive to air content variations. The AWP technique for air content measurement showed a moderate correlation with the pressure method (R² = 0.654 for static measurements), with accuracy influenced by concrete consistency. The study highlights the potential of these automated techniques for real-time concrete quality control, while also revealing limitations related to mix composition variations and calibration requirements. These findings contribute to the ongoing development of more precise and reliable automated measurement systems for fresh concrete properties, supporting the move towards advanced quality control methods.